Evaluation of the Cohesive Strength Between Resin Composite and Light-curing Characterizing Materials - Pucci, Cesar Rogerio [UNESP]; Barcellos, Daphne Camara; Palazon, Milena Traversa [UNESP]; Borges, Alessandra Buhler [UNESP]; da Silva, Melissa Aline; de Paiva Goncalves, Sergio Eduardo [UNESP] (Quintessence Publishing Co Inc, 2012)
Purpose: To evaluate the cohesive strength between composite and different light-curing characterizing materials (LCCM), which were prepared using the intrinsic technique.Materials and Methods: One hundred composite specimens were made by using a prefabricated Teflon device, and a layer of LCCM was applied at the interface. The specimens were divided into 5 groups (n = 20): group 1 (control), no LCCM was used; group 2: application of White Kolor Plus Pigment (Kerr) LCCM; group 3: White Tetric Color Pigment (Ivoclar/Vivadent) LCCM; group 4: Brown Kolor Plus Pigment (Kerr) LCCM; group 5: Black Tetric Color Pigment (Ivoclar/Vivadent) LCCM. All materials were used according to the manufacturers' instructions. Specimens were submitted to a tensile test in a universal testing machine (EMIC DL-200MF) to evaluate the cohesive strength at the composite interface. Data were subjected to one-way ANOVA and Tukey's test (alpha = 5%).Results: ANOVA showed a p-value = 0.0001, indicating that there were significant differences among the groups. The mean values in MPa (+/- standard deviation) obtained for the groups were: G1: 28.5 (+/-2.74)a; G2: 23.5 (+/-2.47)b; G3: 20.3 (+/-2.49)b; G4: 10.5 (+/-2.40)c; G5: 9.66 (+/-3.06)c. The groups with the same letters presented no significant differences. The control group presented statistically significantly higher cohesive strengths when compared to the other groups. The groups in which Brown Kolor Plus Pigment and Black Tetric Color Pigment LCCM were used showed significantly lower cohesive strengths when compared to the groups in which White Kolor Plus Pigment and White Tetric Color Pigment LCMM were used.Conclusion: The use of LCCM produced with the intrinsic technique reduced the cohesive strength of composite.
Keywords: composite; cohesive strength; light-curing characterizing materials